2017
DOI: 10.1155/2017/2606271
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer and Its Treatment: Novel Treatment Approaches with Emphasis on Nanotechnology

Abstract: The life expectancy in the Western world is increasing for a long time, which is the courtesy of a higher life standard, a more thorough hygiene, and, of course, the progress of modern medicine. Nevertheless, one of the illnesses that still proves to be a great challenge regardless of the recent advancements in medicine is cancer. Skin cancer is, according to the World Health Organization, the most common malignancy for the white population. The beginning of the paper offers a brief overview of the latest avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 194 publications
(303 reference statements)
0
88
0
2
Order By: Relevance
“…For example, they should be more effective, cheaper, and without any risk to patient life, even if they do not improve patient' s quality of life. To accomplish patient safety, and for good patient compliance, an ideal treatment should be developed with an improved overall treatment efficiency, a very low possible toxicity, and a specific targeted site (91). Nanotechnology-based formulations can provide all of the above, and their efficacy can be further improved when ornamented with targeting moieties, for instance, specific antibodies (92) or targeted delivery payload (93)(94)(95).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, they should be more effective, cheaper, and without any risk to patient life, even if they do not improve patient' s quality of life. To accomplish patient safety, and for good patient compliance, an ideal treatment should be developed with an improved overall treatment efficiency, a very low possible toxicity, and a specific targeted site (91). Nanotechnology-based formulations can provide all of the above, and their efficacy can be further improved when ornamented with targeting moieties, for instance, specific antibodies (92) or targeted delivery payload (93)(94)(95).…”
Section: Resultsmentioning
confidence: 99%
“…They can incorporate nucleic acids and other organic or inorganic molecules into their aqueous lumen (85-89) and can be used for targeted, controlled drug release (90)(91)(92)(93)(94)(95)(96).…”
Section: Liposomes and Niosomesmentioning
confidence: 99%
“…Our study was designed to evaluate the sensitivity of direct reflectance scanning for the detection of tumor cells in tissue and excision borders in histological sections using anti-EGFR-conjugated GNPs. The superior absorption properties of GNPs have already been utilized for photothermal therapy [43] and other methods of selective cancer therapy, as demonstrated in glioblastomas [40,41], even though there is risk of damage to neighboring tissue. Previous studies also presented diffuse reflectance measurements for a cancer diagnosis [44][45][46], but they did not use nanoparticles as contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005 Australia report that 50-60/100000, are affected by the malignancy melanoma (Garbe et al, 2008). In Slovenian, the human population both male and female in the year 2012 (male-23, 1/100000 and in female-23, 8/100000) the new strategy which holds for Slovenian has 700 new patients with malignancy melanoma (Orthaber et al, 2017). In 2010 research 13200 new cases of malignant melanoma are found yearly.…”
Section: Melanomamentioning
confidence: 99%